Mammal Records from Briscoe, Dickens, Hall, and Motley Counties, Texas - Howell, Eric K.; Duplechin, Ryan M.; Larsen, Peter A.; Hanson, J. Delton; Anwarali, F. A.; Larsen, Roxanne J.; Chambers, Ryan R; Bradley, Robert D. (2009)
We conducted fieldwork in 2008 that resulted in the identification of 18 new mammal records from three counties (Dickens, Hall, and Motley) in northwest Texas. An additional 13 county records collected from 1956-2005 (including from Briscoe County) were identified after an examination of specimens housed in the Natural Science Research Laboratory of the Museum of Texas Tech University. Collecting efforts such as these provide important natural history data that can be used in future assessments of the mammalian diversity within Texas.